An experience of facility based management at one of the malnutrition treatment centre in district Baran of Rajasthan, India - Mulla, Shakila; Gupta, Pankaj Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: To assess performance of one of the Malnutrition Treatment Centre (MTC) in district Baran of Rajasthan. India. Methods: An observational prospective study was conducted at MTC where 132 Severe Acute Malnutrition (SAM) children were recruited. Their socio-demographic details and anthropometric measurements were recorded. These SAM children were followed till the period of 4 follow-up visits to measure their weight. MTC performance indicators were assessed. Results: Majority of SAM children belong to age group less than 2 years, gender female, caste OBC (Other Backward Class), SC (Scheduled Caste) and ST (Scheduled Tribe). ASHAs (Accredited Social Health Activists) are playing key role in referring them to MTC. Death rate was 0%, cure (recovery) rate 42.4%, defaulter rate 25.8%, mean length of stay (days) at MTC was 8.04 and mean weight gain was 5.926 g/kg/day. Performance indicators are significantly affected by length of stay at MTC. Follow-up rate was poor with no significant weight gain observed after discharge. Conclusions: MTCs are effective in saving lives of SAM children but not in maintaining long term control on malnutrition.